MARKETING ANALYSIS OF TENGGIRI FISH BASRENG, RANCAEKEK, BANDUNG - Junianto, Junianto; Nishfi, Dede; F, Rival; S, Revanza; T, Radhidia (Agripreneur : Jurnal Pertanian Agribisnis, 2024)
Basreng are one of the popular processed fish products in Indonesia, known for their savory taste and chewy texture. Micro, small, and medium enterprises (MSMEs) such as "Guligah" Basreng in Rancaekek, Bandung Regency, play a crucial role in local economic development. A comprehensive analysis is needed to understand the potential and challenges of MSMEs in producing and marketing Basreng made from mackerel fish in the area. Basreng has a broad market due to its high nutritional content and delicious taste, making a significant contribution to the regional economy. In this context, research employs quantitative methods with observations and interviews to analyze Basreng enthusiasts in driving MSMEs in Indonesia. The results show that "Guligah" Basreng can sell its products significantly every day, directly contributing to increased employment and serving as a vital factor in local economic development. Thus, Basreng not only emerges as a popular food choice but also holds substantial potential in supporting the growth and sustainability of MSMEs and the local economy.Keywords: Sweet Potato, Variety, Source of Potassium.